Effectiveness of the antifungal black seed oil against powdery mildews of cucumber (Podosphaera xanthii) and barley (Blumeria graminis f.sp. hordei) - Hafez, Yasser M. (Acta Biologica Szegediensis, 2008)
When cucumber and barley leaves were sprayed with 0.5% black seed oil (BSO), rapeseed oil (R oil) and parafine oil (P oil), disease severity of the powdery mildew of cucumber (Podosphaera xanthii) was reduced from 52% (control) to 7.7% (BSO), 18.6% (R oil) and 20% (P oil). Similarly the disease severity of barley powdery mildew (Blumeria graminis f.sp. hordei) was greatly reduced from 63.4% (control) to 9.4% (BSO), 16% (R oil) and 16.4% (P oil). Oils inhibited the conidial germination of cucumber and barley powdery mildews to 29-30.7, 35-38 and 37-41% respectively, as compared to control (58-65%). Furthermore, mycelial growth of the pathogen was severely restricted after application of BSO and other oils. Levels of hydrogen peroxide (H2O2) and superoxide (O2.-) as well as the activity of the antioxidant enzymes in the treated leaves with oils and untreated (control) were measured and determined. H2O2 and O2.-levels slightly increased, however some antioxidants are decreased such as dehydroascorbate reductase (DHAR) but other enzymes were increased such as ascorbate peroxidase (APX) and glutathione S transferase (GST). It can be concluded that the protective effect of oils against powdery mildews resulted mainly from the inhibition of conidial germination and suppression of the mycelial growth of the pathogens and there is slight activation of the host defence mechanisms. Therefore, it is important to giving more attention to BSO and other oils which have effectiveness against powdery mildew pathogens as an alternative control methods which safety and suitable for healthy and organic food production.